Global Citizenship among Thai Citizens: Insights and Future Directions - Kaewmano, Jaruwan (Thai Social Science Journal, 2025)
This research article is part of the research project From Thai Citizens to Democratic Global Citizens for Sustainable Development. It pursues three objectives 1) to examine the characteristics of global citizenship among Thai citizens 2) to investigate key factors influencing the development of global citizenship awareness, and 3) to propose strategies for strengthening global citizenship among Thai people to support sustainable development. The research employed a mixed-methods approach, collecting questionnaire data from 1,500 Thai participants aged 18 and above, complemented by document analysis, in-depth interviews, and focus group discussions with relevant stakeholders. The study assessed global citizenship across three dimensions: knowledge, engagement, and expression. The findings indicate that Thai citizens demonstrate a moderate level of global citizenship awareness. Despite a sound understanding of the interdependencies between national and global matters, their commitment to the global community and subsequent actions for the collective global good remain limited. Differences in global citizenship levels among respondents are attributed to age, education, occupation, government policy, and cultural context. The study found that existing Thai environmental policies lack substantive and procedural stringency, consequently affecting the continuity and seriousness of implementation. Furthermore, Thailand's educational system for fostering Global Citizenship Awareness remains unclear, lacking conceptual clarity, standardized processes, and coherent administrative direction. Accroding to the fidings, this article proposes that cultivating Global Citizenship Awareness requires establishing a clear framework, process, and indicators within the basic education curriculum. Crucially, teachers' capacity and understanding must be developed to effectively integrate global citizenship concepts into instruction. This will serve as a crucial foundation for driving long-term sustainable development policies.